Complementary Effects of Surgery and Pexidartinib in the Management of Patients with Complex Diffuse-Tenosynovial Giant Cell Tumor - Nicholas M. Bernthal; R. Lor Randall; Lauren N. Zeitlinger; Erik J. Geiger; John H. Healey (Case Reports in Orthopedics)
Tenosynovial giant cell tumor (TGCT) is a rare neoplasm of the joint synovium that has a wide clinical spectrum including pain and stiffness in the affected joint, joint swelling, periarticular erosions, and cartilage loss, which can severely impact quality of life. The mainstay treatment for TGCT has been surgery involving partial or total synovectomy using arthroscopic or open techniques. However, surgical resection alone is associated with high recurrence rates, particularly in diffuse-TGCT (D-TGCT) cases. The 3 cases presented here summarize a combination approach (surgery+pexidartinib [tyrosine kinase inhibitor]) in patients with previously unresectable or inoperable D-TGCT. Case 1-Hip. A 29-year-old male was treated with pexidartinib prior to surgery, resulting in tumor reduction. A left total hip arthroplasty (THA) was then performed with a lack of recurrence in 12 months postoperative, and the patient currently on pexidartinib treatment. Case 2-Foot. A 35-year-old female, nearly a decade following a left foot mass resection, was treated with pexidartinib following disease recurrence. A decrease in soft tissue lesions at the midfoot and decreased marrow enhancement at the first metatarsal head were seen within 4–5 months of pexidartinib treatment; the patient is currently on pexidartinib (400 mg/day) with improved symptom control. Case 3-Knee. A 55-year-old male patient received pexidartinib pre- and postoperatively. A reduction in swelling and the size of the popliteal cyst was significant and maintained, with the synovial disease growing when pexidartinib was discontinued. Surgery and adjuvant therapy eliminated the disease as of the last follow-up visit (11 months postoperative). These cases provide a unique perspective based on tumor location, type/timing of treatment strategy, and patient outcomes. Optimal treatment strategies for this debilitating disease may entail utilizing a combination approach (surgery+systemic treatment) to reduce surgical morbidity and the risk of postoperative disease recurrence.